Unlocking the export potential of Indian millets for global food security - Sankara, N R; Hemalatha, S; Deepa, N; Anandhi, V; Padma, R S; Kowsalya, S (Plant Science Today, 2025)
Millets are gaining renewed importance in India due to their nutritional richness and ability to thrive in adverse climatic environments. This study evaluates the export performance of three major millets: ragi (finger millet), bajra (pearl millet) and jowar (sorghum) using exports as a key indicator. Export data from 2014 to 2024 was analysed using two primary methods: the Compound Annual Growth Rate (CAGR), to assess year-on-year growth in export value and quantity and Markov chain analysis, to examine the evolution of trading relationships with importing countries. The findings indicate that bajra showed the most consistent progress in both export value and volume. Ragi experienced a slight decline in volume but a significant increase in value, likely due to higher unit prices or value-added product exports. Jowar, despite having the lowest volume, recorded the highest increase in export value, reflecting emerging but uncertain demand. The most stable importing countries were identified as Saudi Arabia, Nepal and Libya. Overall, the results suggest that India has strong potential to enhance millet exports by expanding value-added offerings, entering new markets and strengthening trade relationships with key importers.